The spectrum of paracetamol (acetaminophen) overdose: clinical and epidemiological studies. Issue 632 (June 1978) - Hamlyn, A. N.; Douglas, A. P.; James, O.
Abstract : In a regional survey of paracetamol overdose, 201 patients were admitted to hospital over 12 months. Chronic alcoholism was present in 10% of cases. Over 25% of patients were females aged 20 years or less. Initial blood paracetamol levels were in the toxic range in 16% and histologically severe liver damage eventually found in 20% of those biopsied. This finding corresponded to a serum aspartate aminotransferase of 600 i.u./l or more. Renal failure severe enough to require peritoneal dialysis developed in 1%. Elevated serum amylase was recorded in 22% of a 108-patient subset. Evidence of myocardial damage was found in 11.6% of an eighty-six patient subset. An unfavourable prognosis was indicated by a prothrombin ratio of 20% or less and hepatic coma, the overall mortality being 3.5%. The apparent safety of this useful analgesic is compromized by its widespread employment in parasuicide. This, the insidious and delayed onset of toxicity in overdose and ineffectiveness of late treatment argues for controlling availability to the general public.